Glioblastoma hijacks neuronal mechanisms for brain invasion - Venkataramani, Varun; Yang, Yvonne; Schubert, Marc Cicero; Reyhan, Ekin; Tetzlaff, Svenja; Wißmann, Niklas; Botz, Michael; Soyka, Stella; Beretta, Carlo Antonio; Pramatarov, Rangel; Fankhauser, Laura; Garofano, Luciano; et al. (Cell, 2022)
Glioblastomas are incurable tumors infiltrating the brain. A subpopulation of glioblastoma cells forms a functional and therapy-resistant tumor cell network interconnected by tumor microtubes (TMs). Other subpopulations appear unconnected, and their biological role remains unclear. Here, we demonstrate that whole-brain colonization is fueled by glioblastoma cells that lack connections with other tumor cells and astrocytes yet receive synaptic input from neurons. This subpopulation corresponds to neuronal and neural-progenitor-like tumor cell states, as defined by single-cell transcriptomics, both in mouse models and in the human disease. Tumor cell invasion resembled neuronal migration mechanisms and adopted a Lévy-like movement pattern of probing the environment. Neuronal activity induced complex calcium signals in glioblastoma cells followed by the de novo formation of TMs and increased invasion speed. Collectively, superimposing molecular and functional single-cell data revealed that neuronal mechanisms govern glioblastoma cell invasion on multiple levels. This explains how glioblastoma’s dissemination and cellular heterogeneity are closely interlinked.
Das PDF enthält zusätzlich einen Anhang von 31 Seiten
Gesehen am 25.08.2022